Private label brands (plbs) for online third-party marketplace: buying intention among Malaysian young adults - Sawanah Mumin (2023)
Private label brands (PLBs) or the retailers’ brand is not a new retail strategy. However, advancement of technology and the changes in consumers’ lifestyle have led to the growth of online retailers such as the third-party marketplace platforms. PLB has become a recent trend among the third-party marketplace platforms such as Lazada, Shoppe, eBay and Taobao to explore the potential of PLBs. However, examination of the online PLBs is lacking. The purpose of this study is to examine Malaysian young adults’ purchase intention towards PLBs for online third-party marketplace platforms. Young consumers are found to display different responses and behaviours toward marketing stimuli compared to the other generation cohort, PLB could serve as an effective brand building effort and attraction. Building on the theories of cue utilization, UTAUT2 and self-congruency, this study examines characteristics related to individual, store, PLBs and online platform in influencing consumer attitudes and purchase intention. Purposive sampling technique was adopted, and 385 questionnaires were collected among Malaysian young adults aged between 15-30 years old who are considered as heavy internet users and generated 271 usable responses (70% response rate) via google form/Facebook messenger/email. The Statistical Package for Social Science (SPSS) and Partial Least Square – Structural Equation Modeling (PLS-SEM) 3.0 path modelling via SmartPLS were used for data analysis. Overall, twenty-nine relationships were tested in this study. Twenty were found to be significant, while nine were found not significant. For store and PLB related characteristics: four were found significant with attitude (perceived quality, perceived product similarity, perceived risk and PLB image), while one found do not have significant relationship (store loyalty). For individual related characteristics: frugality, familiarity with PLB, social influence and trust were found significant, while price and brand consciousness as well as consumer innovativeness are not significant with attitude. Performance and effort expectancy were found significant with purchase intention, however hedonic motivation found do not have significant relationship for online platform related characteristics. In addition, for mediation effect, twelve relationships were found significant (perceived quality, perceived product similarity, perceived risk, PLB image, frugality, familiarity with PLB, social influence and trust), and four were found not significant (store loyalty, consumer innovativeness, price and brand consciousness). Self-congruity found significantly moderated the relationship between attitude and purchase. In conclusion, the study shows that young adults’ attitude and intention can be predicted through the cues that influence them, technology that was useful in their daily activities as well as their consideration towards elements that congruence with their-self. The findings of this study benefit the academic and marketing practitioners by expanding on previous literature about consumer behaviour and help retailers to enhance their sales through target group. Therefore, through this study, the retailers can focus on young adults’ preferences towards their brands, products, and services such as quality, similarity, image, familiarity, social influence, and trust as well as performance and effort expectancy for online business activities where these elements play a significant role for consumers to choose PLBs for online third-party marketplace to build a strong attitude and intention to buy.